Logistics as a science: Central research questions in the era of the fourth industrial revolution - Werner Delfmann; Michael Ten Hompel; Wolfgang Kersten; Thorsten Schmidt; Wolfgang Stölzle (Logistics Research, 2018)
Fourth Industrial Revolution or Industry 4.0 denotes a fundamental change on how production and business in general is perceived and organized. This paper questions the role of logistics within this context and raises a claim for a central role in future. It is a revision of a current position of the Scientific Advisory Board of Bundesvereinigung Logistik (BVL). Based on the insight that Logistics 4.0 is a crucial element for the implementation of Industry 4.0 three hypotheses are derived. In further elaboration, the paper introduces a total of 11 key research questions that are of central importance to the research community.
Keywords: 650; Logistics 4.0; Industry 4.0; Decentralization; Digitization; Human collaboration